Donor acute kidney injury and short-term graft outcome in renal transplantation - Jacobi, Johannes; Rebhan, Dirk; Heller, Katharina; Velden, Joachim; Hilgers, Karl Friedrich; Wullich, Bernd; Eckardt, Kai-Uwe; Amann, Kerstin Ute (Clinical Transplantation, 2014)
With increased waiting times for kidney transplantation, marginal organs from expanded criteria donors (ECD) are increasingly offered for allocation. In addition to ECD status, donors may have suffered from acute kidney injury (AKI) prior to organ procurement.In this retrospective cohort study, we studied short-term allograft function in 517 kidney transplants performed between the years 2008-2014. Recipients of allografts from deceased organ donors were categorized as standard criteria donors (SCD) or ECD with or without AKI defined by RIFLE criteria.Of 382 deceased donations, 174 (45.5%) were classified as ECD and 63 (16.5%) fulfilled AKI criteria. Donor creatinine on hospital admission was similar, whereas creatinine before organ procurement differed (p < 0.001). Despite these differences, serum creatinine and eGFR at discharge and after one yr showed only minor differences between kidneys with or without AKI. In multivariate linear regression analyses, donor AKI was not a predictor of one-yr allograft function.Given the poor prognosis of dialysis patients and the increase in waiting time, kidneys from SCD and ECD donors with AKI should be allocated for transplantation. In case of ECD donors with AKI, recipients should be informed about the possibility of permanent non-function or early graft loss.
EVALuna2:3714

Genetic variants in the genes of the stress hormone signalling pathway and depressive symptoms during and after pregnancy - Schneider, Michael; Engel, Anne; Fasching, Peter; Haeberle, Lothar; Binder, Elisabeth B.; Voigt, Franziska; Grimm, Jennifer; Faschingbauer, Florian; Eichler, Anna; Dammer, Ulf; Rebhan, Dirk; Amann, Manuela; et al. (BioMed Research International, 2014)
The aim of this study was to investigate whether single nucleotide polymorphisms (SNPs) in genes of the stress hormone signaling pathway, specifically FKBP5, NR3C1, and CRHR1, are associated with depressive symptoms during and after pregnancy.The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for the assessment of maternal and fetal health including the assessment of depressiveness. The German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) was completed at three time points in this prospective cohort study. Visit 1 was at study entry in the third trimester of the pregnancy, visit 2 was shortly after birth, and visit 3 was 6-8 months after birth. Germline DNA was collected from 361 pregnant women. Nine SNPs in the above mentioned genes were genotyped. After construction of haplotypes for each gene, a multifactorial linear mixed model was performed to analyse the depression values over time.EPDS values were within expected ranges and comparable to previously published studies. Neither did the depression scores differ for comparisons among haplotypes at fixed time points nor did the change over time differ among haplotypes for the examined genes. No haplotype showed significant associations with depressive symptoms severity during pregnancy or the postpartum period.The analysed candidate haplotypes in FKBP5, NR3C1, and CRHR1 did not show an association with depression scores as assessed by EPDS in this cohort of healthy unselected pregnant women.
EVALuna2:17356